COMPARATIVE EVALUATION OF PARAMETERS SINGLE LAPAROSCOPIC ACCESS AT ANATOMICAL RESEARCH AND SPIRAL COMPUTED TOMOGRAPHY - Ахметзянов, Рустам Габдылоханович; Развозжаев, Юрий Борисович; Баранов, Андрей Игоревич; Фаев, Алексей Алексеевич; Данильченко, Иван Юрьевич; Алонцев, Андрей Владимирович (Medicine in Kuzbass, 2019)
Objective. Parameters of a single laparoscopic access (LA) to the base of the appendix, the neck of the gallbladder and the duodenal bulb (DB).Purpose of the study – to conduct a comparative analysis of the parameters of a single LA to the base of the appendix, the neck of the gallbladder and the DB, obtained in an anatomical experiment and during a spiral computed tomography (CT).Methods. The parameters of a single LA to the base of the appendix, the neck of the gallbladder and the DB were assessed using the CT method in 101 patients and in an anatomical study on 98 non-fixed cadavers. The parameters of the four median accesses and access in the left iliac region to the base of the vermiform process, umbilical and epigastric accesses to the neck of the gall bladder, vertical subcostal, left subcostal and umbilical accesses to the DB were evaluated.Results. A comparative analysis of the parameters of access to the appendix, gallbladder, DB according to anatomical studies and CT revealed statistically significant differences in most access criteria.The area of their application. Justification of a single LA based on an objective assessment of access parameters.Conclusions: 1. CT allows to study the objective characteristics of the parameters of a single LA to the appendix, gall bladder and DB. 2. CT allows in vivo, pre-operative, individual assessment of the parameters of LA to the appendix, gallbladder and DB. 3. CT allows to reduce the invasiveness of a single LA to the appendix, gallbladder and DB by choosing the location of the access, taking into account its optimal parameters.
Keywords: parameters of LA; single LA; minimally invasive access; CT; anatomical experiment